Identification of HES4 as a novel prognostic marker and therapeutic target in hepatocellular carcinoma - Yungang Liu; Ying Shen; Peipei Luo; Shaoxian Wu; Yue Wang; Jianzhong Deng; Linghui Deng; Fang Wang; Jianhua Jin; Jingting Jiang (Discover Oncology)
Abstract Hairy and enhancer of Split 4 (HES4) is thought to have a substantial impact on the pathogenesis and progression of malignancies. However, the prognostic significance and mechanism of HES4 have not been reported in Hepatocellular carcinoma (HCC). A comprehensive bioinformatics analysis of HES4 expression, clinicopathological characteristics, tumor microenvironment status, and drug sensitivity were performed based on TCGA, GTEx, and GEO. Paired HCC samples and cell lines were used to validate the dysfunction of HES4 in vitro. The expression of HES4 at both mRNA and protein levels was significantly upregulated in HCC tissues. High level of HES4 was associated with unfavorable outcomes. Enrichment analysis demonstrated strong associations of HES4 with HCC progression pathways. In addition, elevated HES4 expression was positively correlated with increased sensitivity to various chemotherapy drugs and associated with resistance to immunotherapy. As a transcription factor, the target genes regulated by HES4 were mostly risky genes, and a novel prediction model based on HES4 target genes was generated for HCC risk stratification. The AUCs of 1-, 3-, and 5-year year overall survival (OS) were 0.829, 0.732, and 0.700, respectively. HES4 overexpression is associated with poor clinical outcomes and tumor progression. HES4 may serve as a novel prognostic marker and therapeutic target in HCC.